Analysis of the Essential Oils of Nepeta straussii, N. amoena, N. haussknechtii and N. speciosa from Iran: Analysis of the Essential Oils of Nepeta straussii, N. amoena, N. haussknechtii and N. speciosa from Iran - Sefidkon, Fatemeh; Zakerian, Fatemeh; Moradi, Aiuob; Kalvandi, Ramezan; Bidarlord, Mahmoud; Asgari, Fatemeh (Iranian Journal of Pharmaceutical Sciences, 2023)
The aerial parts essential oils of nine populations of four Nepeta species (N. straussi Hausskn. & Bornm., N. amoena Stapf., N. haussknechtii Bornm. and N. speciosa Boiss. & Noë), from Iran, were analyzed by gas chromatography, flame ionization detector (GC-FID), and mass spectrometric detection (GC/MS). In the oil of one population of N. straussi, 1,8-cineole (40.1%) was the main constituent. In contrast, the oil of the second population consisted of germacrene D (11.6%), caryophyllene oxide (11.9%), and n-nonadecane (10.3%) as major compounds. Caryophyllene oxide (36.2%) in one population and hexadecanoic acid (33.4%) in another population of N. amoena were the major compounds. In the oils of two populations of N. haussknechtii, 1,8-cineole (45.1% and 48.6%) was the main constituent, while 4aα-7α-7aα-nepetalacton (26.7%) and 1,8-cineole (24.5%) were major components in the oil of third population. In the essential oil of one population of N. speciosa, 4aα-7β-7aα-nepetalacton (74.8%) and the other population, 1,8-cineole (32.3%), were the main constituents. Therefore, in addition to variations between essential oil compositions of different Nepeta species, there are variations in the oil composition of one Nepeta species from different localities that may be due to climatic conditions or having the potential to form chemotypes.